Non-invasive neurally adjusted ventilatory assist versus nasal continuous positive airway pressure for premature infants: a systematic review and meta-analysis - Yuan Yuan; Fang He; Dehua Wu; Hongmei Zou (European Journal of Medical Research)
Abstract Objective The purpose of this study was to compare the benefits of non-invasive neurally adjusted ventilatory assist (NIV-NAVA) versus Nasal continuous positive airway pressure (NCPAP) as respiratory support for premature infants. Methods Literature on NIV-NAVA and NCPAP as respiratory support of premature infants was comprehensively searched from PubMed, Web of Science, Embase, China National Knowledge Infrastructure (CNKI), Wanfang Database, and VIP database. The search time was from the establishment of the database to June 20, 2023. Meta-analysis was performed by RevMan 5.4 software. The rate of extubation failure, need for intubation, surfactant therapy, as well as the adverse outcomes of bronchopulmonary dysplasia (BPD), necrotizing enterocolitis (NEC), and pneumothorax were compared between NIV-NAVA group and NCPAP group. Results 5 eligible randomized controlled trials involving 326 newborns were included. No significant difference was found in the above 7 indexes between NIV-NAVA and NCPAP. Conclusions Compared with NCPAP, NIV-NAVA has not obtained significant advantages in premature infants yet. However, NIV-NAVA is still a potential non-invasive mechanical ventilation method, which needs more research to confirm.